A study on the status quo and influencing factors of ICU nurses’ knowledge, attitude and practice towards physical restraints in general hospitals in Guangxi (广西壮族自治区ICU护士实施身体约束知信行的现状调查及影响因素分析) - MA Qiang (马强); LI Gaoye (李高叶); LIAO Tingting (廖婷婷); YU Qin (玉琴); HUANG Xiaobo (黄晓波); WEI Xiu (韦秀); XIE Haijuan (谢海娟) (中西医结合护理)
Objective To explore the status quo of ICU nurses' knowledge, attitude and practice of physical restraints use in general hospitals in Guangxi, and to provide a theoretical basis for clinical training and quality control. Methods A simple random sampling method was used to select ICU nurses from Grade III and Grade II hospitals in Guangxi, including 2 Grade III hospitals and 3 Grade II hospitals, with a total of 201 ICU nurses. The knowledge, attitude and practice status of nurses on physical restraints use were investigated by using a physical restraints knowledge, attitude and behavior questionnaire, and the influencing factors were analyzed. Results The total score and scores of knowledge dimension, attitude dimension, and behavior dimension were (135. 08±18. 07), (68. 70±9. 49), (20. 73±4. 82), (45. 66±8. 95), respectively, indicating a low-to-medium level awareness of physical restraints among ICU nurses in general hospitals in Guangxi. There were statistically significant differences in the level of knowledge, attitude and practice of ICU nurses with different hospital levels, ICU working years, and ICU specialist qualifications (P＜0. 05). Conclusion ICU nurses in Guangxi have a more positive attitude towards physical restraint, and their knowledge and behavior level need to be strengthened urgently. ICU managers should improve the physical restraint training mechanism, types and teams of ICU nurses, strengthen relevant knowledge and skills training according to the different characteristics of nurses, build positive attitudes and emotions through enhanced knowledge, promote behavioral changes, and improve the development of physical restraint specialization. (目的 探讨广西壮族自治区ICU护士身体约束知信行现状, 为临床开展相关的培训及质控提供理论依据。方法 采用简单随机抽样法, 选取广西壮族自治区三级甲等、二级甲等共5所医院的ICU护士共201名作为研究对象, 采用“ICU护士实施身体约束知信行评估量表”调查护士对患者实施身体约束的知识、态度和行为现状, 并分析影响因素。结果 广西壮族自治区ICU护士身体约束知信行总分、知识维度、态度维度、行为维度得分分别为(135. 08±18. 07)分、(68. 70±4. 82)分、(45. 66±8. 95)分, 整体上为中等偏低水平。不同医院等级、ICU工作年限、有无ICU专科资质的ICU护士身体约束知信行水平差异有统计学意义(P＜0. 05)。结论 广西壮族自治区ICU护士身体约束态度较为积极, 知识及行为水平亟待加强。ICU管理者应健全ICU护士身体约束培训机制、种类和队伍, 根据护士的不同特征强化相关知识与技能培训, 通过增强知识建立积极态度和情感, 促使行为改变, 促进身体约束专科化发展。)